CONVERSATIONAL IMPLICATURE IN MABA BELO SELEMBAR DIALOGUE OF KARONESE CULTURE - Sembiring, Rony Arahta; Manik, Sondang; Pasaribu, Arsen Nahum; Surbakti, Tiara Sari; Ketaren, Selfiyani (University of Kuningan, 2024)
Abstract: Implicit meaning or supplementary meaning of the speaker's speech is revealed by implicature analysis, a technique employed in pragmatics. This research is expected to provide a deeper understanding of implicatures in the Karonese language and can assist in preserving the Karonese language and culture. The research method used in this research is the descriptive-analytical method. The data used in this study were obtained from video recordings of Maba Belo Selambar conversations taken from youtube. Descriptive qualitative analysis was used to analyze the social phenomena in depth and comprehensively, explaining or describing these phenomena in detail. The data analysis would be based on the implications developed by Grice in exploring cooperative communication in conversation and using Jakobson's theory of language function to see the implications of the conversation. The writer found 35 pieces of data that consist of implicacies based on the function of language. After analyzing the data, the researcher finds that the metalinguistic function (15 data) is the most dominant, followed by the comparative function (11 data), the referential function (6 data points), the phonic function (2 data) and the poetic function (1 data). The author found that the use of language functions in metalinguistics was more likely to be used because the speakers on both sides threw structured, ethical language codes at the event.